Association between Salivary Fructosamine, Plasma Glycated Hemoglobin, and Plasma Glucose Levels among Type II Diabetes Mellitus and Nondiabetic Individuals—A Cross-sectional Study - Kandavel, Sadhana; Kumar, P.D Madan (European Journal of Dentistry, 2019)
Objective The study was aimed to determine the association between salivary fructosamine and plasma glycated hemoglobin, plasma fasting and postprandial glucose levels among patients suffering from type II diabetes mellitus and nondiabetic healthy individuals.Materials and Methods The cross-sectional study was conducted in a hospital setting. A total of 100 participants were included, with 50 participants in each group—group I (patients with type II diabetes mellitus) and group II (nondiabetic healthy individuals). Blood and saliva samples were collected to estimate the levels of the blood and salivary parameters. Depending upon the normality, appropriate tests were used—t-test and Mann–Whitney U test were used for continuous data. Pearson chi-square test and Fisher's exact test were used for discrete data. To test for any positive association between salivary and blood parameters, simple linear regression was carried out.Results The study results showed that group I had significantly higher levels of salivary fructosamine when compared to group II (p < 0.001). In groups I and II a significant positive association was observed between salivary fructosamine and plasma glycated hemoglobin (group I, r-value 0.893; group II, r-value 0.307).Conclusion The overall study results showed that salivary fructosamine levels were significantly higher in patients with diabetes when compared to nondiabetic individuals. Also, positive correlation was observed between salivary fructosamine, plasma fasting, plasma postprandial, and plasma glycated hemoglobin among both the groups.
Keywords: noninvasive; saliva; fructosamine; diabetes mellitus; glycated hemoglobin